2019
DOI: 10.3386/w25459
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Debt, Firm Size and Financial Fragility in Emerging Markets

Abstract: for thoughtful comments and suggestions. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 3 publications
2
22
0
1
Order By: Relevance
“…Our results also suggest that the debt overhang‐investment linkage is stronger for large firms, in which the sensitivity of investment to debt overhang is about twice as high as small firms. This further supports a literature that documents the important role of large firms in driving aggregate economic activity and financial risks, both for EMDEs and advanced economies (e.g., Alfaro et al, 2019; Gabaix, 2011). These findings also point to policy implications that may warrant additional attention on large firms, such as the orderly resolution of their debt‐related defaults.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results also suggest that the debt overhang‐investment linkage is stronger for large firms, in which the sensitivity of investment to debt overhang is about twice as high as small firms. This further supports a literature that documents the important role of large firms in driving aggregate economic activity and financial risks, both for EMDEs and advanced economies (e.g., Alfaro et al, 2019; Gabaix, 2011). These findings also point to policy implications that may warrant additional attention on large firms, such as the orderly resolution of their debt‐related defaults.…”
Section: Introductionsupporting
confidence: 87%
“…Debt overhang arises when accumulated debts may be excessive relative to the earnings flowing from new investments, and hence may lead firms to underinvest in positive net present value projects. Indeed, corporate earnings and returns have slowed during the postcrisis period in the context of the economic slowdown in many EMDEs (Alfaro et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Firm size, leverage level, audit quality and firm profitability are the most famous characteristics that have been consider in the literature. It was proved that firm size and leverage level has a positive correlation with the financial distress (Alfaro et al, 2019). On the other side, audit quality and firm profitability are inversely correlated to the financial distress (Du and Lai, 2018).…”
Section: Financial Distressmentioning
confidence: 98%
“…Daskalakis and Psillaki [2008] reported that firms that invest more in fixed assets feel less distressed. Recently, Alfaro et al [2019] determined the importance of total assets in defining the association between financial leverage and financial fragility in emerging markets. They further insisted that large firms are more fragile and equally crucial for economic growth.…”
Section: Moderating Role Of Fixed Collateralsmentioning
confidence: 99%